Middle-age dementia risk scores and old-age cognition: a quasi-experimental population-based twin study with over 20-year follow-up - Paula Iso-Markku; Jaakko Kaprio; Noora Lindgren; Juha O. Rinne; Eero Vuoksimaa (United Kingdom, 2025)
Middle-age risk scores predict cognitive impairment, but it is not known if these associations are evident when controlling for shared genetic and environmental factors. Using two risk scores, self-report educational-occupational score and Cardiovascular Risk Factors, Aging and Dementia (CAIDE), we investigated if twins with higher middle-age dementia risk have poorer old-age cognition compared with their co-twins with lower risk.
We used a population-based older Finnish Twin Cohort study with middle-age questionnaire data (n=15 169, mean age=52.0 years, SD=11.8) and old-age cognition measured via telephone interview (mean age=74.1, SD=4.1, n=4302). Between-family and within-family linear regression analyses were performed.
In between-family analyses (N=2359), higher educational-occupational score was related to better cognition (B=0.76, 95% CI 0.69 to 0.83) and higher CAIDE score was associated with poorer cognition (B=-0.73, 95% CI -0.82 to -0.65). Within twin-pair differences in educational-occupational score were significantly related to within twin-pair differences in cognition in dizygotic (DZ) pairs (B=0.78, 95% CI 0.25 to 1.31; N=338) but not in monozygotic (MZ) pairs (B=0.12, 95% CI -0.44 to 0.68; N=221). Within twin-pair differences in CAIDE score were not related to within twin-pair differences in cognition: DZ B=-0.38 (95% CI -0.90 to 0.14, N=343) and MZ B=-0.05 (95% CI -0.59 to 0.49; N=226).
Middle-age dementia risk scores predicted old-age cognition, but within twin-pair analyses gave little support for associations independent of shared environmental and genetic factors. Understanding genetic underpinnings of risk score-cognition associations is important for early detection of dementia and designing intervention trials.